Epoxy resin composition, cured resin, prepreg and fiber-reinforced composite material

The epoxy resin composition, combining specific ratios of bisphenol and novolac-type epoxy resins with red phosphorus and aluminum hydroxide, addresses the challenges of flame retardancy and viscosity in carbon fiber composites, resulting in a lightweight material with excellent mechanical properties and non-halogen gas emission.

JP7655227B2Active Publication Date: 2025-04-02TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021574088
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-29
Filing Date
2021-01-28
Publication Date
2025-04-02
Estimated Expiration
2041-01-28

AI Technical Summary

Technical Problem

Existing epoxy resin compositions for carbon fiber-reinforced composite materials face challenges in achieving sufficient flame retardancy without emitting halogen gases, and balancing viscosity to facilitate fiber impregnation, often leading to sticky prepregs with poor handling properties.

Method used

An epoxy resin composition comprising 25-45 parts of liquid bisphenol-type and 20-40 parts of phenol novolac-type epoxy resins, combined with red phosphorus and aluminum hydroxide, along with a curing accelerator, to achieve a balanced viscosity and excellent flame retardancy.

Benefits of technology

The composition results in a lightweight, non-halogen gas-emitting fiber-reinforced composite material with superior mechanical properties and processability, ensuring high flame retardancy and stable handling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655227000001
    Figure 0007655227000001
  • Figure 0007655227000002
    Figure 0007655227000002
Patent Text Reader

Abstract

An epoxy resin composition comprises the following components [A] to [E]: [A] epoxy resin, [B] amine-type curing agent, [C] cure accelerator, and [D] red phosphorus. The epoxy resin composition contains, per 100 mass parts for the total amount of [A], 25-45 mass parts of [A1] a liquid bisphenolic epoxy resin and 20-40 mass parts of [A2] a phenol novolac-type epoxy resin, and has a content ratio of [E] to [D] ([E] / [D]) of at least 1. Provided are a light-weight fiber-reinforced composite material that exhibits an excellent flame retardancy and mechanical properties and does not produce halogen gas during combustion, and an epoxy resin composition that has a viscosity suitable for obtaining the fiber-reinforced composite material as well as prepregs.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin composition suitable as a matrix resin for fiber-reinforced composite materials, more particularly to an epoxy resin composition capable of giving a lightweight cured resin product having excellent flame retardancy and mechanical properties, a prepreg containing the epoxy resin composition, and a fiber-reinforced composite material comprising the cured resin product and reinforcing fibers. [Background technology]

[0002] Fiber-reinforced composite materials using thermosetting resins such as epoxy resins as matrix resins, particularly carbon fiber-reinforced composite materials using carbon fibers, are used in a wide range of fields, including sports fields such as golf clubs, tennis rackets, and fishing rods, structural and interior materials for aircraft and vehicles, and reinforcement of concrete structures, due to their light weight and excellent mechanical properties. In recent years, carbon fibers have been used in the housings of electronic and electrical devices such as laptops and video cameras, not only because of their excellent mechanical properties but also because they are conductive, and are useful for making the housings thinner and reducing the weight of the devices. Such carbon fiber-reinforced composite materials are often obtained by laminating prepregs obtained by impregnating reinforcing fibers with thermosetting resins.

[0003] Among the various applications of carbon fiber reinforced composite materials, there is a strong demand for materials to have flame retardancy so that they do not ignite and burn in the event of a fire, particularly in structural materials and interior materials for aircraft and vehicles, etc. Also, in electronic and electrical equipment applications, there is a demand for flame retardant materials to prevent accidents in which housings or parts ignite and burn due to heat generated inside the equipment or exposure to high temperatures outside.

[0004] In this trend, compounds containing halogens, such as bromine, in the molecule have been widely used to make fiber-reinforced composite materials flame-retardant.Specific examples include brominated epoxy resins, and flame-retardant epoxy resin compositions that use antimony trioxide as a flame retardant in addition to brominated epoxy resins.

[0005] However, it has been pointed out that the above-mentioned halogen-containing resin compositions and their cured products generate hydrogen halides upon combustion, which may have adverse effects on the human body and the natural environment. Therefore, progress has been made in the development of non-halogen epoxy resin compositions that exhibit excellent flame retardancy without containing halogens.

[0006] As a technology for making halogen-free epoxy resin compositions flame-retardant, a technology for a matrix resin for carbon fiber-reinforced composite materials, which is made of epoxy resin and red phosphorus, has been disclosed (for example, Patent Document 1). This technology does not generate halogen gas, and since the phosphorus content, which acts to impart a flame retardant, contained in red phosphorus is very high, flame retardancy can be obtained without impairing the inherent properties of the epoxy resin even with a small amount added. In addition, as a technology for making halogen-free epoxy resin compositions flame-retardant, a technology for a matrix resin for fiber-reinforced composite materials, which is made of phosphorus-containing epoxy resin, novolac-type epoxy resin, and metal oxide, has been disclosed (for example, Patent Document 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2005-082982 [Patent Document 2] Patent No. 5904194 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the epoxy resin composition and carbon fiber reinforced composite material in which only red phosphorus is blended as a flame retardant, which are the technology of Patent Document 1, do not necessarily satisfy sufficient flame retardancy. In addition, although the technology of Patent Document 2 has the advantage of not generating halogen gas, a large amount of metal oxide must be added to obtain sufficient flame retardancy, and a resin composition containing a large amount of such a flame retardant has a high viscosity, which may make it difficult to impregnate the reinforcing fiber. In addition, if a large amount of low-viscosity epoxy resin is blended to reduce the viscosity during impregnation, the obtained prepreg becomes sticky and the handling property deteriorates, making it difficult to achieve a balance.

[0009] An object of the present invention is to solve the above-mentioned problems in the conventional art and to provide a lightweight fiber-reinforced composite material which has excellent flame retardancy and mechanical properties and does not emit halogen gases upon combustion, and to provide an epoxy resin composition having a viscosity suitable for obtaining such a fiber-reinforced composite material and a prepreg. [Means for solving the problem]

[0010] In order to achieve the above object, the epoxy resin composition of the present invention has the following configuration.

[0011] That is, the epoxy resin composition contains the following components [A] to [E], in which the epoxy resin composition contains 25 to 45 parts by mass of [A1] liquid bisphenol-type epoxy resin and 20 to 40 parts by mass of [A2] phenol novolac-type epoxy resin per 100 parts by mass of the total amount of component [A], and the content ratio of component [E] to component [D] ([E] / [D]) is 1 or more. [A] Epoxy resin [B] Amine-based hardener [C] Curing accelerator [D] Red phosphorus [E] Aluminum hydroxide.

[0012] The cured resin product of the present invention is obtained by curing the above-mentioned epoxy resin composition.

[0013] The prepreg of the present invention is formed by impregnating reinforcing fibers with the epoxy resin composition.

[0014] The fiber-reinforced composite material of the present invention is produced by curing a prepreg. Effect of the Invention

[0015] According to the present invention, it is possible to obtain a lightweight fiber-reinforced composite material which has excellent flame retardancy and mechanical properties and does not emit halogen gas upon combustion, as well as a prepreg and an epoxy resin composition having a viscosity suitable for obtaining such a fiber-reinforced composite material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The epoxy resin composition, the cured resin, the prepreg, and the fiber-reinforced composite material of the present invention will be described below.

[0017] The epoxy resin composition of the present invention contains [A] an epoxy resin, [B] an amine-based curing agent, [C] a curing accelerator, [D] red phosphorus, and [E] aluminum hydroxide.

[0018] The component [A] in the present invention includes [A1] a liquid bisphenol type epoxy resin and [A2] a phenol novolac type epoxy resin. In this case, the component [A] may be a mixture of only [A1] and [A2], or may include other epoxy resins, and is not particularly limited, but [A1] is preferably a bisphenol A type epoxy resin or a bisphenol F type epoxy resin. In particular, it is preferable that [A1] contains a bisphenol A type epoxy resin and a bisphenol F type epoxy resin, and the content ratio of the bisphenol F type epoxy resin to the bisphenol A type epoxy resin (mass ratio represented by bisphenol F type epoxy resin / bisphenol A type epoxy resin) is 1 or less. In the present invention, "liquid" refers to one that shows fluidity at 25°C.

[0019] In the epoxy resin composition of the present invention, the content of the epoxy resin [A1] is 25 to 45 parts by mass relative to 100 parts by mass of the total amount of [A], and the content of the epoxy resin [A2] is 20 to 40 parts by mass relative to 100 parts by mass of the total amount of the component [A]. This allows the epoxy resin composition to be combined with reinforcing fibers to form a prepreg, and when the prepreg is heat-cured to form a fiber-reinforced composite material, high flame retardancy and heat resistance can be imparted.

[0020] In the present invention, when the contents of [A1] and [A2] are within the above ranges, the tackiness of the epoxy resin composition and the flame retardancy required for the fiber reinforced composite material can be compatible. In addition, from the viewpoint of the balance between flame retardancy and tackiness, the content ratio of [A2] to [A1] (mass ratio represented by [A2] / [A1]) is preferably within the range of 0.5 to 1.5.

[0021] Commercially available liquid bisphenol A type epoxy resins include jER (registered trademark) 825, jER (registered trademark) 826, jER (registered trademark) 827, jER (registered trademark) 828, and jER (registered trademark) 834 (all manufactured by Mitsubishi Chemical Corporation), EPICLON (registered trademark) 850 (manufactured by DIC Corporation), Epotohto (registered trademark) YD-128 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), DER-331, and DER-332 (all manufactured by The Dow Chemical Company).

[0022] Commercially available bisphenol F type epoxy resins include jER (registered trademark) 806 and jER (registered trademark) 807 (both manufactured by Mitsubishi Chemical Corporation), EPICLON (registered trademark) 830 (manufactured by DIC Corporation), and Epotohto (registered trademark) YDF-170 (manufactured by Nippon Steel Chemical & Material Co., Ltd.).

[0023] [A1] may be used alone or in combination with other epoxy resins. In particular, when a large amount of flame retardant is added to impart high flame retardancy, it is preferable to combine liquid bisphenol A type epoxy resin and liquid bisphenol F type epoxy resin in order to maintain the tackiness of the resin composition.

[0024] Commercially available phenol novolac epoxy resins for use in [A2] include jER (registered trademark) 152 and jER (registered trademark) 154 (both manufactured by Mitsubishi Chemical Corporation), EPICLON (registered trademark) N-740, EPICLON (registered trademark) N-770, and EPICLON (registered trademark) N-775 (both manufactured by DIC Corporation).

[0025] The components [A1] and [A2] may each be used alone or in combination of two or more types.

[0026] The epoxy resin [A] in the present invention may contain an epoxy resin other than the epoxy resin [A1] or [A2]. For example, a solid bisphenol A type epoxy resin, a solid bisphenol S type epoxy resin, a glycidyl ether type epoxy resin such as an aliphatic epoxy resin, a glycidyl ester type epoxy resin, a glycidyl amine type epoxy resin, a rubber-modified epoxy resin, or the like may be contained.

[0027] The component [B] in the present invention is an amine-based curing agent. The amine-based curing agent is a compound having a nitrogen atom in the curing agent molecule.

[0028] Such a curing agent is not particularly limited as long as it contains a nitrogen atom in the molecule. For example, aromatic polyamine compounds having active hydrogen such as 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, and diethyltoluenediamine, and fatty acids having active hydrogen such as diethylenetriamine, triethylenetetramine, isophoronediamine, bis(aminomethyl)norbornane, bis(4-aminocyclohexyl)methane, and dimer acid esters of polyethyleneimine can be used. Examples of the amines include aromatic amines, modified amines obtained by reacting these amines having active hydrogen with compounds such as epoxy compounds, acrylonitrile, phenol and formaldehyde, and thiourea, tertiary amines not having active hydrogen such as N,N-dimethylaniline, N,N-dimethylbenzylamine, 2,4,6-tris(dimethylaminomethyl)phenol and 1-substituted imidazole, dicyandiamide, tetramethylguanidine, polycarboxylic acid hydrazides such as adipic acid hydrazide and naphthalenecarboxylic acid hydrazide, and Lewis acid complexes such as boron trifluoride ethylamine complex.

[0029] The amine curing agent [B] in the present invention preferably has thermal activation latency for the sake of stability in the resin compounding process, storage stability at room temperature, or stability against the thermal history experienced in the process of impregnating carbon fibers with the epoxy resin composition for carbon fiber reinforced composite materials. Here, thermal activation latency means the property that the agent is in a low activity state as it is, but undergoes a phase change or chemical change when subjected to a certain thermal history, thereby changing into a highly active state.

[0030] The amine-based curing agent [B] of the present invention is preferably dicyandiamide. Dicyandiamide is a particulate curing agent that is hardly soluble in epoxy resin at 25°C, but dissolves when heated to 100°C or higher and reacts with epoxy groups. In other words, it is a latent curing agent that is insoluble at low temperatures and soluble at high temperatures.

[0031] The component [C] in the present invention is a curing accelerator, and is used to enhance the curing activity of the amine-based curing agent [B]. For example, dicyandiamide can be suitably used in combination with urea derivatives such as 3-phenyl-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU), 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 4,4'-methylenebis(diphenyldimethylurea), and 2,4-toluenebis(3,3-dimethylurea) or imidazole derivatives as a curing accelerator. Dicyandiamide alone requires a temperature of about 170 to 180°C for curing, whereas a resin composition using such a combination can be cured at 80 to 150°C. In particular, a combination of dicyandiamide and a compound having two or more urea bonds in one molecule is preferred. As a compound having two or more urea bonds in one molecule, 4,4'-methylenebis(diphenyldimethylurea) or 2,4-toluenebis(3,3-dimethylurea) is preferred. When these compounds are used, they can be cured at 150 to 160°C in about 2 to 30 minutes, which is preferable.

[0032] Component [D] in the present invention is red phosphorus. The flame retardant effect of red phosphorus is believed to be due to the promotion of carbide formation of phosphorus atoms, and is greatly influenced by the phosphorus content in the epoxy resin composition. In the present invention, in order to obtain flame retardancy more effectively, the content of component [D] is preferably 2 to 10 parts by mass, more preferably 5 to 10 parts by mass, per 100 parts by mass of the total amount of component [A] epoxy resin.

[0033] Here, the red phosphorus used is not only untreated red phosphorus, but also red phosphorus whose surface is coated with a metal hydrate and a resin to enhance stability. Examples of the metal hydrate include aluminum hydroxide, magnesium hydroxide, zinc hydroxide, and titanium hydroxide. There is no particular limitation on the type of resin and the amount of coating, but the resin is preferably a phenolic resin, an epoxy resin, or polymethyl methacrylate, which has a high affinity with the epoxy resin used in the present invention. In addition, in order to suppress the generation of phosphine gas during high-temperature kneading, the amount of coating is preferably 1% by mass or more relative to the red phosphorus. The amount of coating is preferably as large as possible in terms of stability, but preferably does not exceed 20% by mass in terms of flame retardancy.

[0034] The component [E] in the present invention is aluminum hydroxide. The flame retardant effect of aluminum hydroxide is believed to be due to the endothermic effect that accompanies the decomposition and generation of moisture during combustion.

[0035] The content ratio of component [E] to component [D] (mass ratio represented by [E] / [D]; the same applies below) is 1 or more. This makes it possible to suppress the decomposition of char at the early stage of combustion due to the endothermic heat generated during the thermal decomposition of component [E], and therefore to more effectively promote the formation of char by red phosphorus. In addition, the content ratio of component [E] to component [D] ([E] / [D]) is preferably less than 25 in order to achieve a balance between the char formation by red phosphorus and the endothermic effect of aluminum hydroxide.

[0036] As the component [E], a particulate material can usually be used, and the particle size is not particularly limited, but from the viewpoint of flame retardancy and dispersibility, the average diameter calculated from the arithmetic mean is preferably 0.8 to 10.0 μm, more preferably 0.8 to 2.0 μm. The particle size can be measured by a laser scattering particle size distribution measurement. Depending on the composition of the epoxy resin composition, from the balance between flame retardancy and tackiness, the content of the component [E] is preferably 5 to 50 parts by mass, more preferably 10 to 50 parts by mass, and even more preferably 15 to 45 parts by mass, relative to 100 parts by mass of the total amount of the epoxy resin component [A].

[0037] In addition, the epoxy resin composition for carbon fiber reinforced composite materials of the present invention may contain one or more other flame retardants in combination to improve flame retardancy.

[0038] Other flame retardants include compounds containing nitrogen atoms such as melamine cyanurate, melamine sulfate, and guanidine sulfamate; metal hydrates such as magnesium hydroxide, calcium hydroxide, and tin hydroxide; metal oxides such as zinc borate, zinc hydroxystannate, and magnesium oxide; silicone resins; and silicone oils.

[0039] The epoxy resin composition for carbon fiber reinforced composite materials of the present invention can contain a thermoplastic resin [F] for the purpose of controlling viscoelasticity and imparting toughness.

[0040] Examples of such thermoplastic resins include polymethyl methacrylate, polyvinyl acetals such as polyvinyl formal and polyvinyl butyral, polyvinylpyrrolidone, polymers containing at least two types of components selected from aromatic vinyl monomers, vinyl cyanide monomers, and rubber-like polymers, polyamides, polyesters, polycarbonates, polyarylene oxides, polysulfones, polyethersulfones, polyimides, and phenoxy resins. Among these, polyvinyl formals and polyethersulfones are preferably used because they have good compatibility with many types of epoxy resins and have a large effect of controlling the flowability of epoxy resin compositions for carbon fiber reinforced composite materials. Commercially available products of polyvinyl formals include "Vinylec (registered trademark)" K (manufactured by JNC Corporation), and commercially available products of polyethersulfones include "Sumikaexcel (registered trademark)" PES5003P (manufactured by Sumitomo Chemical Co., Ltd.) and "VIRANTAGE (registered trademark)" VW-10700RFP (manufactured by Solvay).

[0041] In the epoxy resin composition for carbon fiber reinforced composite materials of the present invention, the preferred amount of the thermoplastic resin component varies depending on the type of thermoplastic resin, but in the case of polyvinyl formal, it is preferably 0.5 to 10 parts by mass, and in the case of polyethersulfone, it is preferably 5 to 30 parts by mass, per 100 parts by mass of the epoxy resin. Within this range, both the drapeability of the prepreg and the flame retardancy of the carbon fiber reinforced composite material can be achieved.

[0042] When the epoxy resin composition for carbon fiber reinforced composite materials used in the present invention is used for prepreg applications, it is preferable that the viscosity at 40°C is 1500 to 30000 Pa·s and the viscosity at 60°C is 10 to 700 Pa·s from the viewpoint of processability such as tack and drape. When the viscosity at 40°C is 1500 to 30000 Pa·s, the shape retention of the prepreg is high, and when the viscosity at 60°C is 10 to 700 Pa·s, high impregnation of the reinforcing fibers during molding is obtained, so that the fiber content is stable and preferable. The viscosity at 60°C is more preferably 65 to 85 Pa·s. When the viscosity at 40°C exceeds 30000 Pa·s, the epoxy resin composition for carbon fiber reinforced composite materials may cause fainting during the film formation process or unimpregnated parts may occur during the carbon fiber impregnation process.

[0043] The viscosities at 40°C and 60°C referred to here are determined by the following method. That is, a dynamic viscoelasticity measuring device such as ARES (manufactured by TA Instruments Japan) is used, and the epoxy resin composition is set using flat parallel plates with a diameter of 40 mm so that the distance between the upper and lower plates is 1 mm. After confirming that the temperature has reached 40°C, measurements are performed in torsion mode (angular frequency: 3.14 rad / s) with a simple temperature rise of 5°C / min, and the complex viscosities η at 40°C and 60°C are calculated. * This is what is required.

[0044] The more carbonized material (char) remaining after thermal decomposition of the cured product obtained by curing the epoxy resin composition used in the present invention, the higher the flame retardancy, and therefore the more preferable it is. Specifically, it is preferable that the char generation rate at 600°C is reached when heated from room temperature at a simple temperature rise of 10°C / min under an air flow of 200 ml / min is 30% or more, and that at 900°C is reached when heated from room temperature at a simple temperature rise of 60°C / min under a nitrogen flow of 200 ml / min is 25% or more. The char generation rate referred to here is a value expressed by (mass (g) of thermal decomposition residue at a predetermined temperature) / (mass (g) of the cured epoxy resin before measurement)×100 using a thermogravimetric analyzer TG-DTA.

[0045] The glass transition temperature of the cured product is preferably 90 to 250°C, more preferably 90 to 220°C, and even more preferably 95 to 200°C. If the glass transition temperature is less than 90°C, the heat resistance of the cured product is insufficient, and the carbon fiber reinforced composite material may be distorted, and may be deformed when used in a high temperature environment. If the glass transition temperature exceeds 250°C, the cured product tends to be brittle, and the tensile strength and impact resistance of the carbon fiber reinforced composite material may be reduced. The glass transition temperature here is the midpoint temperature determined according to JIS K7121 (1987) using a differential scanning calorimeter (DSC).

[0046] In the prepreg of the present invention, it is preferable to use carbon fibers as the reinforcing fibers. By using carbon fibers as the reinforcing fibers, it is possible to provide the fiber-reinforced composite material with excellent flame retardancy, strength, and impact resistance.

[0047] The epoxy resin composition of the present invention can be used as a fiber-reinforced composite material in combination with reinforcing fibers. Carbon fibers can be preferably used as reinforcing fibers, and any known carbon fibers can be used as the carbon fibers, but those having a strand strength of 3000 MPa or more and 7500 MPa or less and an elastic modulus of 200 GPa or more and 450 GPa or less in a strand tensile test are preferably used. The strand tensile test refers to a test carried out based on JIS R7601 (1986).

[0048] The number of carbon fiber filaments is preferably 2,500 to 50,000, and more preferably 2,800 to 40,000, from the viewpoints of preventing the fiber arrangement from meandering and facilitating resin impregnation during prepreg production or molding.

[0049] The carbon fibers used in the present invention are classified into polyacrylonitrile-based, rayon-based, and pitch-based carbon fibers. Among them, polyacrylonitrile-based carbon fibers having high tensile strength are preferably used. Polyacrylonitrile-based carbon fibers can be produced, for example, through the following process. A spinning dope containing polyacrylonitrile obtained from a monomer mainly composed of acrylonitrile is spun by a wet spinning method, a dry-wet spinning method, a dry spinning method, or a melt spinning method. The solidified yarn after spinning is made into a precursor through a spinning process, and then carbon fibers can be obtained through processes such as flame retardation and carbonization.

[0050] Commercially available carbon fibers include "TORAYCA (registered trademark)" T700G-24K, "TORAYCA (registered trademark)" T300-3K, and "TORAYCA (registered trademark)" T700S-12K, each having a tensile modulus of 230 GPa, "TORAYCA (registered trademark)" T800G-24K, "TORAYCA (registered trademark)" T800S-24K, each having a tensile modulus of 294 GPa, and "TORAYCA (registered trademark)" T1100G-24K, each having a tensile modulus of 324 GPa (all manufactured by Toray Industries, Inc.).

[0051] The form and arrangement of the carbon fibers can be appropriately selected from long fibers aligned in one direction, woven fabric, etc., but in order to obtain a carbon fiber reinforced composite material that is lightweight and has a higher level of durability, it is preferable that the carbon fibers are in the form of continuous fibers such as long fibers aligned in one direction (fiber bundles) or woven fabric, etc. The long fibers referred to here are those with an average fiber strand length of 10 mm or more.

[0052] The carbon fiber bundles used in the present invention preferably have a single fiber fineness of 0.2 to 2.0 dtex, more preferably 0.4 to 1.8 dtex, from the viewpoint of preventing damage to the carbon fiber bundles during twisting or during the resin composition impregnation treatment step and of sufficiently impregnating the carbon fiber bundles with the resin composition.

[0053] The prepreg of the present invention can be produced by various known methods, for example, a wet method in which the matrix resin made of the epoxy resin composition of the present invention is dissolved in an organic solvent selected from acetone, methyl ethyl ketone, methanol, etc. to reduce the viscosity and is then impregnated into reinforcing fibers, or a hot melt method in which the matrix resin is heated to reduce the viscosity without using an organic solvent and then is impregnated into reinforcing fibers.

[0054] In the wet method, the reinforcing fibers are immersed in a liquid containing a matrix resin, then pulled out, and the organic solvent is evaporated using an oven or the like to obtain a prepreg. In the hot melt method, a matrix resin that has been reduced in viscosity by heating is directly impregnated into the reinforcing fibers, or a release paper sheet with a resin film (hereinafter sometimes referred to as a "resin film") is first produced by first coating the matrix resin on release paper or the like, and then the resin film is placed on both sides or one side of the reinforcing fibers, and the reinforcing fibers are impregnated with the matrix resin by heating and pressurizing.

[0055] As a method for producing the prepreg of the present invention, a hot melt method in which the matrix resin is impregnated into the reinforcing fibers without using an organic solvent is preferably used, since substantially no organic solvent remains in the prepreg.

[0056] The prepreg of the present invention has a reinforcing fiber amount per unit area of ​​70 to 2000 g / m 2 It is preferable that the amount of reinforcing fibers is 70 to 2000 g / m 2 Within this range, the prepreg has excellent drapeability, and when molding a fiber-reinforced composite material, the number of prepreg layers required to obtain a predetermined thickness is appropriate, resulting in excellent workability.

[0057] The mass content of the reinforcing fibers in the prepreg of the present invention is preferably 30 to 90 mass%, more preferably 35 to 85 mass%, and further preferably 40 to 80 mass%. When the mass content of the reinforcing fibers in the prepreg is 30 mass% or more, a fiber-reinforced composite material excellent in specific strength and specific elastic modulus can be obtained, and the amount of heat generated during curing when molding the fiber-reinforced composite material can be suppressed. When the mass content of the reinforcing fibers in the prepreg is 90 mass% or less, the reinforcing fibers are sufficiently impregnated with the matrix resin, and a fiber-reinforced composite material without voids can be obtained.

[0058] The fiber-reinforced composite material of the present invention can be produced, for example, by laminating the above-mentioned prepregs of the present invention in a predetermined form and applying heat and pressure to cure the matrix resin. Methods for applying heat and pressure include press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, etc.

[0059] Furthermore, fiber-reinforced composite materials can also be produced without using prepregs by directly impregnating reinforcing fibers with the epoxy resin composition of the present invention and then heat-curing the fibers, for example by molding methods such as the hand lay-up method, the filament winding method, the pultrusion method, the resin injection molding method, and the resin transfer molding method.

[0060] The carbon fiber reinforced composite laminate obtained by laminating and curing the prepreg of the present invention has a flame retardancy measured at a thickness of 1 mm, and a maximum heat release rate of 70 kW m in the heat release test (OSU method) in accordance with FAR25.853 (Appendix F, Part IV). -2 less than 50 kW m -2 It has high flame retardancy of less than 100%. EXAMPLES

[0061] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. Materials used in the examples and comparative examples are shown below.

[0062] <Component [A1]: Liquid bisphenol type epoxy resin> "jER (registered trademark)" 828 (liquid bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation) "EPICLON (registered trademark)" 830 (bisphenol F type epoxy resin, manufactured by DIC Corporation).

[0063] <Component [A2]: Phenol novolac type epoxy resin> "jER (registered trademark)" 154 (phenol novolac type epoxy resin, manufactured by Mitsubishi Chemical Corporation).

[0064] <Component [A] other than component [A1] and component [A2]: epoxy resin> "jER (registered trademark)" 1001 (solid bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation).

[0065] <Component [B]: Amine-based hardener> Dicy7T (dicyandiamide, manufactured by Mitsubishi Chemical Corporation).

[0066] <Component [C]: Curing accelerator> "Omicure (registered trademark)" 24 (2,4'-toluenebis(3,3-dimethylurea), manufactured by PTI Japan Co., Ltd.).

[0067] <Component [D]: Red phosphorus> "NovaRed (registered trademark)" 120UF (surface-coated red phosphorus, phosphorus content 75% by mass, manufactured by Rinkagaku Kogyo Co., Ltd.).

[0068] <Component [E]: Aluminum hydroxide> C-301N (aluminum hydroxide, average particle size: 1.5 μm, manufactured by Sumitomo Chemical Co., Ltd.).

[0069] <Component [F]: Thermoplastic resin> "Vinylec (registered trademark)" K (polyvinyl formal, manufactured by JNC Corporation). "VIRANTAGE (registered trademark)" VW-10700RFP (polyethersulfone, manufactured by Solvay).

[0070] <Carbon fiber> "TORAYCA (registered trademark)" T700SC-12K (tensile strength 4.9 GPa, tensile modulus 230 GPa, elongation 2.1%, fiber specific gravity 1.80, manufactured by Toray Industries, Inc.).

[0071] (1) Method for preparing epoxy resin composition In a kneading device, epoxy resin corresponding to component [A], red phosphorus corresponding to component [D], aluminum hydroxide corresponding to component [E], and thermoplastic resin corresponding to component [F] listed in Tables 1 and 2 were charged, and then heated and kneaded to dissolve component [F]. Next, the temperature was lowered to 60°C or lower, and Dicy7T corresponding to component [B] and a curing accelerator corresponding to component [C] listed in Tables 1 and 2 were added and stirred to disperse uniformly, to obtain an epoxy resin composition for carbon fiber reinforced composite materials.

[0072] (2) Viscosity measurement of epoxy resin composition The viscosity of the epoxy resin composition was measured using a dynamic viscoelasticity device ARES-G2 (manufactured by TA Instruments Co., Ltd.) Using flat parallel plates with a diameter of 40 mm, the epoxy resin composition was set so that the distance between the upper and lower plates was 1 mm. After confirming that the temperature had reached 40°C, the viscosity was measured in torsion mode (angular frequency: 3.14 rad / s) with a simple temperature increase of 5°C / min up to 60°C, and the viscosities at 40°C and 60°C were obtained.

[0073] Based on this measurement, the evaluation criteria for tackiness and drapeability were set as follows.

[0074] Evaluation criteria (tack and drape) A: "The viscosity at 40°C is 1500~30000 Pa·s, and the viscosity at 60°C is 10~700 Pa·s." B: "Viscosity at 40°C is less than 1500 Pa·s and viscosity at 60°C is 10 to 700 Pa·s," or "Viscosity at 40°C is 1500 to 30000 Pa·s and viscosity at 60°C is less than 10 Pa·s," or "Viscosity at 40°C is 1500 to 30000 Pa·s and viscosity at 60°C exceeds 700 Pa·s." C: "Viscosity at 40°C is less than 1500 Pa·s and viscosity at 60°C is less than 10 Pa·s," or "Viscosity at 40°C is greater than 30,000 Pa·s," or "Viscosity at 40°C is less than 1500 Pa·s and viscosity at 60°C is greater than 700 Pa·s."

[0075] (3) Flame retardancy evaluation of cured epoxy resin The epoxy resin composition prepared in (1) was degassed in a vacuum, and then cured under the prescribed curing conditions in a mold set to a thickness of 2 mm using a 2 mm Teflon (registered trademark) spacer to obtain a 2 mm thick epoxy resin cured product. Flame retardancy was evaluated using a thermogravimetric analyzer TG-DTA (WS003 system by Bruker AXS). A test piece of about 10 mg was cut out from the epoxy resin cured product, and the char generation rate (%) at 600°C was reached when the temperature was simply increased from room temperature at a rate of 10°C / min under an air flow of 200 ml / min, and the char generation rate (%) at 900°C was reached when the temperature was simply increased from room temperature at a rate of 60°C / min under a nitrogen flow of 200 ml / min were used as indicators of flame retardancy. The char generation rate referred to here is a value expressed as (mass (g) of thermal decomposition residue at a prescribed temperature) / (mass (g) of epoxy resin cured product before measurement)×100.

[0076] Based on this measurement, the evaluation criteria for flame retardancy were set as follows:

[0077] Evaluation criteria (flame retardancy) S: "Char generation rate under air flow is 30% or more, and char generation rate under nitrogen flow is 3.5% or more." A: "The char generation rate under air flow is 30% or more, and the char generation rate under nitrogen flow is 25% or more but less than 35%." B: "Char generation rate under air flow is 30% or more, and char generation rate under nitrogen flow is less than 25%" or "Char generation rate under air flow is less than 30% and char generation rate under nitrogen flow is 25% or more." C: "Char generation rate under air flow is less than 30%, and char generation rate under nitrogen flow is less than 25%."

[0078] (4) Prepreg Preparation A predetermined amount of the epoxy resin composition prepared in (1) above was coated on a release paper to prepare a resin film. This resin film was set in a prepreg making machine and the fiber mass per unit area was 150 g / m 2The carbon fibers are aligned in one direction in a sheet shape so that resin films are laid on both sides of the carbon fibers, and the fibers are impregnated with the resin composition by heating and pressurizing, so that the weight of the carbon fibers becomes 150 g / m 2 A unidirectional prepreg with a matrix resin mass fraction of 33% was produced. The carbon fiber used was Torayca (registered trademark) T700SC-12K.

[0079] (5) Fabrication of carbon fiber reinforced composite laminates Seven plies of the unidirectional prepreg prepared in (4) above were laminated in a (0 / 90 / 0 / 90 / 0 / 90 / 0) configuration to produce a 1 mm thick laminate. The laminate was molded in an autoclave at 130°C for 90 minutes under a pressure of 0.6 MPa and a heating rate of 2.5°C / min to produce a 1 mm thick unidirectional laminate. This laminate was cut to a width of 150 mm and a length of 150 mm.

[0080] (6) Heat release test (OSU method) The laminate produced in (5) above was subjected to a heat release test (OSU method) in accordance with FAR25.853 (Appendix F, Part IV) to evaluate the maximum heat release rate.

[0081] Based on this measurement, the evaluation criteria for flame retardancy were set as follows:

[0082] Evaluation criteria (flame retardancy) S: Maximum heat generation rate is 50kW m -2 is less than. A: Maximum heat generation rate is 50kW m -2 More than 70kW m -2 is less than. B: Maximum heat generation rate is 70kW m -2 That's all.

[0083] Example 1 As shown in Table 1, an epoxy resin composition was prepared using jER (registered trademark) 828 as component [A1], jER (registered trademark) 154 as component [A2], jER (registered trademark) 1001 as component [A] other than components [A1] and [A2], Dicy7T as component [B], Omicure (registered trademark) 24 as component [C], Novaled (registered trademark) 120UF as component [D], C-301N as component [E], and Vinylec (registered trademark) K as component [F], and the viscosity and thermogravimetric measurements of the cured resin were performed. In addition, a laminate of a carbon fiber reinforced composite material was prepared using Torayca (registered trademark) T700SC-12K as the carbon fiber, and a heat release test (OSU method) was also performed. The viscosity of the resin composition was sufficient (A) for obtaining a fiber-reinforced composite material and a prepreg, and the flame retardancy of the cured resin and the laminate of the carbon fiber-reinforced composite material was also good (A).

[0084] Example 2 A cured resin and a laminate of a carbon fiber reinforced composite material were produced in the same manner as in Example 1, except that the amount of "jER (registered trademark)" 1001 in component [A] was reduced and "E PICLON (registered trademark)" 830 was added, and the amount of component [E] C-301N was increased from 10 parts by mass to 50 parts by mass. When the properties were evaluated, it was found that the flame retardancy was higher than that of Example 1 (S).

[0085] Example 3 A laminate of a cured resin and a carbon fiber reinforced composite material was produced in the same manner as in Example 2, except that the amount of "jER (registered trademark)" 1001 blended as component [A] was slightly increased and the amount of "EPICLON (registered trademark)" 830 blended was slightly decreased. The properties were evaluated and were equivalent to those of Example 2 and were good.

[0086] Example 4 A laminate of a cured resin and a carbon fiber reinforced composite material was produced in the same manner as in Example 3, except that the amount of "jER (registered trademark)" 1001 mixed as component [A] was slightly increased and the amount of "jER (registered trademark)" 154 mixed was slightly decreased. The properties were evaluated and were equivalent to those of Example 3 and were good.

[0087] Example 5 A laminate of a cured resin and a carbon fiber reinforced composite material was produced in the same manner as in Example 3, except that the amount of "jER (registered trademark)" 1001 mixed as component [A] was slightly increased and the amount of "jER (registered trademark)" 154 mixed was slightly decreased. The properties were evaluated and were equivalent to those of Example 3 and were good.

[0088] Example 6 A laminate of a cured resin and a carbon fiber reinforced composite material was produced in the same manner as in Example 3, except that the amount of "jER (registered trademark)" 1001 mixed as component [A] was slightly reduced and the amount of "jER (registered trademark)" 154 mixed was slightly increased. The properties were evaluated and were equivalent to those of Example 3 and were good.

[0089] Example 7 A laminate of a cured resin and a carbon fiber reinforced composite material was produced in the same manner as in Example 5, except that 10 parts by mass of "VIRANTAGE (registered trademark)" VW-10700RFP was used as component [F]. The properties were evaluated and were equivalent to those of Example 5 and were excellent.

[0090] Example 8 A cured resin and a laminate of a carbon fiber reinforced composite material were produced in the same manner as in Example 2, except that the amount of "jER (registered trademark)" 1001 mixed as component [A] was slightly increased and the amount of "EPICLON (registered trademark)" 830 mixed as component [A] was slightly decreased, and the amount of C-301N mixed as component [E] was slightly decreased. The properties were evaluated and were equivalent to those of Example 2 and were good.

[0091] Example 9 A laminate of a cured resin and a carbon fiber reinforced composite material was produced in the same manner as in Example 5, except that the amount of "Novared (registered trademark)" 120UF blended as component [D] was slightly reduced and the amount of C-301N blended as component [E] was slightly increased. The properties were evaluated and were equivalent to those of Example 5 and were good.

[0092] Example 10 A laminate of a cured resin and a carbon fiber reinforced composite material was produced in the same manner as in Example 5, except that the amount of "Novaled (registered trademark)" 120UF blended as component [D] was slightly reduced and the amount of C-301N blended as component [E] was slightly increased. The properties were evaluated and were equivalent to those of Example 5 and were good.

[0093] Comparative Example 1 A resin composition and a cured resin were prepared in the same manner as in Example 1, except that the component [E] was not included. When the properties were evaluated, the viscosity of the resin composition was good (A), but the flame retardancy of the cured resin was insufficient (B).

[0094] Comparative Example 2 A resin composition and a cured resin were prepared in the same manner as in Example 1, except that component [D] was not included. When the properties were evaluated, the viscosity of the resin composition was good, but the flame retardancy of the cured resin was significantly lower (C) than in Example 1.

[0095] Comparative Example 3 A resin composition and a cured resin were prepared in the same manner as in Example 1, except that the amount of component [D] was reduced from 10 parts by mass to 5 parts by mass and component [E] was not included. When the properties were evaluated, the viscosity of the resin composition was slightly insufficient (B), and the flame retardancy of the cured resin was also insufficient (B).

[0096] Comparative Example 4 A resin composition and a cured resin were prepared in the same manner as in Example 1, except that the amount of component [E] was reduced from 10 parts by mass to 5 parts by mass. When the properties were evaluated, the viscosity of the resin composition was sufficient (A), but the flame retardancy of the cured resin was somewhat insufficient (B).

[0097] Comparative Example 5 A resin composition and a cured resin were prepared in the same manner as in Example 1, except that only "jER (registered trademark)" 154 was used as component [A]. When the properties were evaluated, the flame retardancy of the cured resin was sufficient (A), and the viscosity of the resin composition was slightly insufficient (B).

[0098] Comparative Example 6 A resin composition and a cured resin were prepared in the same manner as in Example 1, except that only "jER (registered trademark)" 828 was used as component [A] and the amount of component "B" was slightly increased. When the properties were evaluated, the flame retardancy of the cured resin was sufficient (A), but the viscosity of the resin composition was significantly lower than that of Example 1 and was insufficient (C).

[0099] Comparative Example 7 A resin composition and a cured resin were prepared in the same manner as in Example 1, except that component [A] contained only 50 parts by mass each of "jER (registered trademark)" 828 and "jER (registered trademark)" 154, and the amount of component "B" was slightly increased. When the properties were evaluated, the flame retardancy of the cured resin was sufficient (A), but the viscosity of the resin composition was significantly lower than that of Example 1 and was insufficient (B).

[0100] Comparative Example 8 A resin composition and a cured resin were prepared in the same manner as in Example 1, except that the amount of component [A1] was changed from 30 parts by mass to 20 parts by mass, the amount of component [A2] was changed from 35 parts by mass to 10 parts by mass, the amount of "jER (registered trademark)" 1001 was changed from 35 parts by mass to 70 parts by mass, and the amount of component "B" was slightly reduced. When the properties were evaluated, the flame retardancy of the cured resin was sufficient (A), but the viscosity of the resin composition had increased significantly compared to Example 1 and was insufficient (C).

[0101] Comparative Example 9 A cured resin and a laminate of a carbon fiber reinforced composite material were produced in the same manner as in Example 3, except that the amount of "jER (registered trademark)" 1001 blended as component [A] was greatly reduced and the amount of "jER (registered trademark)" 154 blended was greatly increased. When the properties were evaluated, the flame retardancy of the cured resin was sufficient (S), but the viscosity of the resin composition was significantly reduced compared to Example 3 and was slightly insufficient (B).

[0102] Comparative Example 10 A cured resin and a laminate of a carbon fiber reinforced composite material were produced in the same manner as in Example 3, except that the amount of "jER (registered trademark)" 1001 blended as component [A] was greatly reduced, the amount of "jER (registered trademark)" 154 blended was slightly reduced, and the amount of "jER (registered trademark)" 828 blended was greatly increased. When the properties were evaluated, the flame retardancy of the cured resin was sufficient (A), but the viscosity of the resin composition was significantly reduced compared to Example 3 and was insufficient (B).

[0103] [Table 1]

[0104] [Table 2]

Claims

1. An epoxy resin composition comprising the following components [A] to [E], wherein the epoxy resin composition contains, relative to 100 parts by mass of a total amount of component [A], 25 to 45 parts by mass of [A1] liquid bisphenol-type epoxy resin and 20 to 40 parts by mass of [A2] phenol novolac-type epoxy resin, and the content ratio of component [E] to component [D] ([E] / [D]) is 1 or greater. [A] Epoxy resin [B] Amine-based curing agent [C] Curing accelerator [D] Red phosphorus [E] Aluminum hydroxide

2. 2. The epoxy resin composition according to claim 1, wherein the content ratio of component [E] to component [D] ([E] / [D]) is less than 25.

3. 3. The epoxy resin composition according to claim 1 or 2, wherein component [A1] comprises a bisphenol F type epoxy resin.

4. The epoxy resin composition according to any one of claims 1 to 3, further comprising a component [F] a thermoplastic resin.

5. 5. The epoxy resin composition according to claim 4, wherein component [F] is polyvinyl formal or polyether sulfone.

6. 6. The epoxy resin composition according to claim 5, wherein component [F] is polyvinyl formal and the content thereof per 100 parts by mass of the total amount of component [A] is 0.5 to 10 parts by mass.

7. 6. The epoxy resin composition according to claim 5, wherein component [F] is polyethersulfone and the content thereof per 100 parts by mass of the total amount of component [A] is 5 to 30 parts by mass.

8. The epoxy resin composition according to any one of claims 1 to 7, comprising 2 to 10 parts by mass of component [D] per 100 parts by mass of the total amount of component [A].

9. The epoxy resin composition according to any one of claims 1 to 8, comprising 5 to 50 parts by mass of component [E] per 100 parts by mass of the total amount of component [A].

10. 10. The epoxy resin composition according to claim 9, wherein the content of component [E] is 15 parts by mass or more and less than 45 parts by mass.

11. 11. The epoxy resin composition according to claim 1, having a viscosity of 1,500 to 30,000 Pa·s at 40° C. and a viscosity of 10 to 700 Pa·s at 60° C.

12. 12. The epoxy resin composition according to claim 1, having a viscosity at 60° C. of 65 to 85 Pa·s.

13. A cured resin product obtained by curing the epoxy resin composition according to any one of claims 1 to 12.

14. A prepreg obtained by impregnating reinforcing fibers with the epoxy resin composition according to any one of claims 1 to 12.

15. A fiber-reinforced composite material obtained by curing the prepreg according to claim 14.

Citation Information

Patent Citations

  • Semiconductor laser device

    JP1984004194A

  • Epoxy resin composition, prepreg, and carbon fiber-reinforced composite material

    JP2010265371A

  • Epoxy resin composition, prepreg and fiber-reinforced composite material

    JP2011148938A

  • Halogen-free flame-retardant epoxy resin composition

    WO1996028511A1

  • Epoxy resin composition for carbon-fiber-reinforced composite material, prepreg, integrated molding, sheet of fiber-reinforced composite material and cabinet for electrical / electronic equipment

    WO2005082982A1